2008
DOI: 10.1177/0741932507312010
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Quality and Stability of the Teaching Force Influence the Research-to-Practice Gap?

Abstract: Although effective practices have been developed to address the needs of a wide range of students with disabilities, evidence suggests a limited use of these practices. Potential contributors to the research-to-practice gap focus on problems with preservice teacher preparation, professional development, and the nature of research. The authors present evidence that the lack of well-qualified special education teachers, the instability of special education teachers in teaching positions (i.e., attrition and migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
120
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(123 citation statements)
references
References 53 publications
3
120
0
Order By: Relevance
“…This research yielded important information pertaining to what middle school general education teachers, based on their preparation, training, and support, were able to do while facing high standards of accountability from outside agencies and school administration (Darling-Hammond;McLeskey & Billingsley, 2008;Smith & Tyler, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This research yielded important information pertaining to what middle school general education teachers, based on their preparation, training, and support, were able to do while facing high standards of accountability from outside agencies and school administration (Darling-Hammond;McLeskey & Billingsley, 2008;Smith & Tyler, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Since implementation of such models is a complex process that is often fraught with unanticipated events, conflicts and resolutions (Aarons & Palinkas, 2007), several concerns should be taken into account to improve the probability that conditions are adequate to implement these practices (McLeskey & Billingsley, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Since most schools employ only a few special education teachers at best and perhaps as many as half of those are either novices in their first few years of teaching or out-offield aspiring special educators (e.g., Boe & Cook, 2006), it can be very difficult to find enough quality field sites to meet every student's needs (Epanchin & Colucci, 2002;Jenkins et al, 2002). Moreover, research on teacher attrition in special education has consistently shown that the number of teaching vacancies that occur each year far outstrips the number of newly qualified graduates prepared to occupy those positions and that many of those who leave their classrooms each year are seasoned veterans (McLeskey & Billingsley, 2008).…”
Section: The Challenges To Community Building Field Experience and Prmentioning
confidence: 99%